Study of the effect of bifonazole concentration on the antifungal activity of vaginal suppositories - T. V. Mielnyk; N. L. Kolycheva (Zaporozhye State Medical University, 2024)
The analysis of the current state of pharmacotherapy for vulvovaginal candidiasis reveals that there is a contemporary need for the development of soft dosage forms for the local treatment of infectious diseases affecting the vulva and vagina. This should be based on azole derivatives that, despite possessing a well-established wide spectrum of antifungal and antibacterial effects, have not been utilized for vaginal administration in domestic formulations. The successful realization of this project would enable the field of domestic dermatology to provide effective, compliant, and affordable drugs for gynecological practice to the general population of Ukraine. Additionally, it would establish a viable alternative to imported pharmacotherapeutic agents. Aim. The purpose of this work is the scientific substantiation of the concentration of bifonazole in suppository compositions for vaginal use. Materials and methods. Research was conducted to investigate the influence of bifonazole concentration ranging from 1 % to 15 % in soft dosage forms for vaginal use. Model compositions were formulated on a polyethylene oxide carrier, considering its solubility. The antifungal activity of the experimental suppository compositions was chosen as the optimization parameter and assessed using the diffusion method in agar against Candida albicans ATCC 885-653. Variance analysis of the results revealed a significant impact of bifonazole concentration on the antimycotic activity of the suppository compositions based on the model polyethylene oxide. Results. The research results show that increasing the concentration of the active pharmaceutical ingredient in suppository masses above 10 % does not lead to a statistically significant increase in their antimycotic activity. Conclusions. As a result of the conducted study on the antifungal effect of suppository masses with bifonazole on a model polyethylene oxide basis, it was found that the concentration of the active pharmaceutical ingredient has a statistically significant effect on the effectiveness of the soft dosage form. It was established that a ten percent concentration of bifonazole, equivalent to 0.3 g of the biologically active substance in vaginal suppositories, provides the optimal level of their antifungal effect.